Kepercayaan dan risiko dalam pemanfaatan teknologi informasi perpajakan - Dean Charlos Padji Dogi; Yenni Mangoting; Sany Sany; Tonny Stephanus Eoh (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2025)
Purpose – This study evaluates the impact of risk and trust on taxpayers' attitudes and intentions regarding tax information technology. As digital transformation in the tax system continues to evolve, understanding the psychological factors influencing technology adoption is crucial for tax authorities. Methods – This study employs a quantitative approach using a survey involving 202 individual taxpayers. Data analysis uses the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method to examine the relationships between variables in the research model. Findings - he results indicate that trust and risk significantly influence taxpayers' attitudes but do not directly impact their intention to use tax information technology. Trust emerges as the most dominant factor in shaping a positive attitude, whereas technological risk plays a greater role in determining negative attitudes. Attitude is found to mediate the effect of trust and risk on the intention to use tax technology. Implications - This study offers strategic guidance for tax authorities on managing technological risks and enhancing trust. By providing this guidance, the study aims to empower tax authorities in supporting digital transformation in the tax sector. Originality - This study brings to light the crucial role of attitude as the key mediator in the relationship between trust, risk, and intention to use tax information technology. This aspect, which has received limited attention in previous research, is a unique and significant contribution of this study.